„Rytuał przejścia” jako kategoria analityczna. Przyczynek do dyskusji nad badaniem rytualnego oblicza rzeczywistości szkolnej - Jaskulska, Sylwia (Wydawnictwo Naukowe UAM, 2013)
The text is part of a debate on the possibility of studying the school through the prism of the anthropological category of "rite". By referring myself to Arnold van Gennep and Victor W. Turner's theory of "rites of passage", I pose a question on the possibility of analysing the current social reality as a series of rites of passage. I touch upon the issue of the universal character of the traditional approach to the "rite of passage" category. I inquire into how much it matches the issues currently formulated in pedagogical research.
The "rite of passage" as an analytic category. A contribution in the discussion on studying the ritual face of school reality
Keywords: rite of passage; ritual face of school; pedagogical research